Marsel: The Past and the Present - Makhtumova Ulbo’lsin (Procedia of Social Sciences and Humanities, 2022)
By the XI-XII centuries, the period of development in Europe began. By this time, handicrafts, trade, and manufacturing had increased in a number of countries in the region. Along with England, Italy and Germany, development has also reached a high level in France. It was at this time that cities in France rose considerably. Especially in the south of France, the economy of the cities began to change dramatically. At the same time, these cities were engaged in intensive trade with Italy and the Middle East through the Mediterranean. Now cities have become not only industrial centers, but also commercial centers. Such cities include Marseille, Toulouse, Lyon and Montpellier. But in these spheres, Marseilles has come a long way.